Is ethnic and cultural-religious heterogeneity a barrier to economic development - Nikolić Goran (Međunarodni Problemi)
The author analyzes the influence of heterogeneity of religious-ethnic structure on economic growth. Most studies show that extraordinary national-religious diversification has a negative impact on economic performance of countries. However, the institutional arrangements that involve a significant degree of decentralization may be a factor of relaxation of ethnic and religious, i.e. political animosity. Positive economic experiences of some institutional and ethnically complex countries show that the single economic policy is possible and that strong the national heterogeneity is not necessarily a negative factor for economic development if there are viable democratic institutions.